Effects of foods preservatives on growth and aflatoxin production of Aspergillus flavus in liquid medium - Thanaboripat, Dusanee (2014)
Benzoic acid, sodium benzoate and potassium metabisulphite at 2.0, 6.0 and 10.0 mg/kg were used to control the growth of Aspergillus flavus and aflatoxin production in liquid medium. Cultures were incubated at room temperature for 6 days with agitation. The results showed that sodoum benzoate at 10 mg/kg reduced the growth of A. flavus by 13 percent and aflatoxin production by 35 percent at day 6. Benzoic acid at 2.0 mg/kg reduced the growth and aflatoxin production by 72 and 87 percent after 6 days whereas benzoic acid at 6.0 and 10.0 mg/kg completely inhibited both mycelial growth and aflatoxin production in liquid medium. Potassium metabisulphite at 2.0, 6.0 and 10.0 mg/kg completely inhibited A. flavus growth and aflatoxin production.